Determinants of Generation Z's Intention to Pay Zakat Digitally - Putri, Alya Rahma; Suwanan, Ahmad Fawaiq (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This research analyzes the factors that influence Generation Z's intention to give zakat through digital platforms by integrating the variables of Zakat Literacy, Social Influence, Trust and Convenience into the development of TPB theory. Data for this study was collected by distributing questionnaires online through Google Form to 196 respondents in Malang City. Respondents were selected by applying purposive sampling technique. Furthermore, the collected data were processed by applying the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using the SmartPLS version 4.1.0.9 application.. The data were then analysed using Partial Least Squares Structural Modeling (PLS SEM) method with the help of SmartPLS Ver 4.1.0.9 software. Based on statistical analysis, Zakat Literacy, Social Influence, Trust, and Convenience are proven to have a positive and significant impact on Generation Z's interest in giving zakat through digital platforms. The implications of these findings emphasise the importance for digital platform providers to improve the development of user friendly features and reduce barriers that may be faced by the public, especially generation Z in Malang City, when using the platform to do zakat. In addition, digital platform providers also need to focus on efforts to build and maintain public trust through transparency, security, and good customer service so that people feel comfortable and trust to use digital platforms. Attention is also needed on marketing strategies and digital campaigns involving influencers, scholars, or social communities.